Electronic Health Record: The Need to Prune - Cooper, Jason G. (2001)
The amount of data that can be stored in an electronic health record could overwhelm even the most committed healthcare professional. We suggest that portions of data be selected for a core electronic health record, while the rest remains available archived in a clinical data repository. The selection of clinical data to archive, or “pruning” as we will refer to this process, must be prefaced with data prioritization. Once this selection and pruning has been performed, the healthcare professional will be presented with a succinct, more manageable, but no less informative electronic health record.